2020
DOI: 10.1155/2020/8768954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms by Which Imeglimin Improves Glucose Homeostasis

Abstract: Despite different classes of antidiabetic medications available for the management of patients with diabetes, efforts are underway to identify novel and safer antihyperglycemic agents with higher potency and increased tolerability. Imeglimin is a promising antidiabetic agent that has shown to have significant antihyperglycemic effects in studies, although it has not been approved yet. There is growing evidence that imeglimin improves glucose homeostasis in the diabetic milieu; however, the precise molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…As described in this review, the mode of action of Imeglimin is unique and distinct compared with other major classes of therapeutic agents. It involves dual effects, both to enhance insulin action and to reverse pancreatic β‐cell dysfunction 5 . The mode of action of Imeglimin is generally well aligned with our current understanding of the pathophysiology of T2D.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As described in this review, the mode of action of Imeglimin is unique and distinct compared with other major classes of therapeutic agents. It involves dual effects, both to enhance insulin action and to reverse pancreatic β‐cell dysfunction 5 . The mode of action of Imeglimin is generally well aligned with our current understanding of the pathophysiology of T2D.…”
Section: Introductionmentioning
confidence: 84%
“…It involves dual effects, both to enhance insulin action and to reverse pancreatic β-cell dysfunction. 5 The mode of action of Imeglimin is generally well aligned with our current understanding of the pathophysiology of T2D. A genetic predisposition plus key environmental factors, principally overnutrition and reduced energy expenditure, are drivers of disease.…”
mentioning
confidence: 88%
“… 153 A recent study reported that imeglemin can improve insulin sensitivity through several molecular pathways including insulin signalling transduction via activating Akt phosphorylation. 154 …”
Section: Future Treatment Optionsmentioning
confidence: 99%
“… 84 , 85 Its unique mechanism of action (MOA) ( Figure 3 ) not only increases glucose-dependant insulin secretion but also reduces IR. 86 , 87 It acts by inhibiting the process of oxidative phosphorylation in the mitochondria of aerobic cells which in turn leads to favourable metabolic effects. 86 Imeglimin counteracts a variety of metabolic disruptions at play in T2DM.…”
Section: Gliminsmentioning
confidence: 99%
“… 86 , 87 It acts by inhibiting the process of oxidative phosphorylation in the mitochondria of aerobic cells which in turn leads to favourable metabolic effects. 86 Imeglimin counteracts a variety of metabolic disruptions at play in T2DM. It accelerates the phosphorylation of Akt (protein kinase B) leading to enhanced insulin signalling 88 and has also been linked to the induction of insulin sensitivity in the β-cells.…”
Section: Gliminsmentioning
confidence: 99%